INCREASE OF RELIABILITY AND EFFICIENCY OF WORK OF DOUBLE-PISTON SOLUTION OF CONCRETE PUMPS WITH DISH VALVES FOR ACCOUNT OF EXCEPTION OF OPPOSITE CURRENT OF CONCRETE MIXTURE (Academic journal Industrial Machine Building Civil Engineering, 2017)
Stable working conditions two-piston растворобетононасосовwith dish-shaped valves proceeding from traffic conditions of a concrete mix and taking into account resistance arising there are defined. The admissible size of a corner of disclosure of the valve α, not allowing emergence of countercurrents of a mix is proved. Keywords:concrete mix, pipeline, mix current, viscosity.